Cutaneous metastatic implantation of ureteric urothelial carcinoma to the glans and prepuce - G.N. Weeratunga (Urology Case Reports, 2023)
Cutaneous deposition of urothelial carcinoma spread through urine is extremely rare, with only four cases described in the literature. It is well known the urothelial carcinoma can spread by implantation via urine into other urothelial lined surfaces, however the phenomena occurring to squamous surfaces is not well described. Herein we describe the only known case of cutaneous implantation of urothelial carcinoma into the prepuce and glans from a ureteric lesion.